“Como se de ventre livre tivesse nascido” : alforrias em Vila Maria do Paraguai/São Luiz de Cáceres, fronteira entre Brasil Bolívia -1860 á 1877 - Coutinho, Maria Auxiliadora de Azevedo (2015)
There is a wide number of publications about African slavery in Brazil, however, when we talk about the way and the use of instruments of Freedom in MatoGrosso Province, in the end of the nineteenth century, it remains little explored with lack of studies that focus on the specificities of the History . The lack of production in this point,is probably due to the fact that the local historiography assign little importance to slave labor in the regional economy, compared with other provinces that have had a significant black presence in prominent economic cycles; There is also more emphasis on studies that favor the region of Cáceresand its characteristics and specificities of defense and expansion of the border of Brazil. Therefore, our study does not intend to break any paradigm, but just bring more information with documentary evidence base about the ways to use the legal instruments forreaching freedom, presenting and contextualizing new sources within the existing historiographical productions. The sources used were the Freedom Letters reunited in the note books from the 1stand 2nd registry of São Luiz de Cáceres, as well as the documentation of the local FORUM from the years of 1860 to 1888, currently available on NUDHEO - Documentation Center Written and Oral Department of History of UNEMAT. By identifying the legal instruments of freedom, we seek its contextualization in all the regional and national historiographical analysis, with emphasis on the specific attitudes of slaves, showing the different strategies that showed how they were agents in the conquest of freedom. These are relevant informations to make an analysis about the paths used to reach freedom by MatoGrosso slaves.